Investigating the Efficacy of Gamification in Enhancing Speaking Skills Among Primary School Students: Case Study of 5th-year Pupils of Ahmed Chatta Primary School - RABHI, Chahinez; Boumédiène, Houda (Faculty of Letters and Foreign Languages Department of English, 2025)
Using gamification is being recognized as a useful technique to improve learning and raise results in language learning. This research, conducted at Ahmed Chatta primary school in Laghouat, aimed to find out the part that gamification plays in promoting primary school pupils’ English-speaking skills while exploring why common teaching approaches can be hard to engage with. The research is focused on determining how well gamification strategies help students improve their speaking skills and their confidence in using English. Thus, the research was designed using quasi-experiment for 24 primary school students from the 5th grade and a questionnaire for their English teachers. Participants were selected through convenience sampling. According to the results of the experiment, students whose lessons included gamelike elements improved their speaking abilities. Besides, implementing gamification seemed to greatly boost students’ readiness and willingness to speak. Speaking activities with game-like elements and role play were the most effective ways to boost speaking skills. Overall, the study found that using gamification wisely greatly helps students learn language skills, mainly by improving speaking abilities. Nevertheless, students will not reach the best potential unless issues related to time, resources and class size are taken into consideration. The research recommends adding game-like elements to language teaching and suggests examining ways to improve practical use as well as how the effects of gamification continue over time. The research offers new insights into how gamification will transform teaching English and highlights possible new opportunities for innovation in education